Analisis Pengaruh Gaya Hidup Hedonisme dan Fear of Missing Out (FOMO) terhadap Perilaku Konsumtif dengan Mediasi Etika Konsumsi Islami pada Generasi Z di Sidoarjo - Elok Faiqoh; Norma Rosyidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid growth of the digital economy in 2025 has significantly changed consumer behavior, especially among Generation Z. Easy access to social media and online shopping platforms has reinforced a hedonistic lifestyle and the Fear of Missing Out (FOMO) phenomenon. This study aims to analyze the influence of a hedonistic lifestyle and FOMO on consumer behavior, with Islamic consumer ethics as an intervening variable among Generation Z in Sidoarjo. This study employed a quantitative approach using a survey method with a questionnaire distributed to 120 respondents. Data were analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM). The study's findings revealed that a hedonistic lifestyle and FOMO have a positive and significant influence on consumer behavior. However, when mediated by Islamic consumer ethics, their influence decreases, suggesting that Islamic consumer ethics can act as a moderating and controlling factor for consumerism among young people. This study contributes to the field of Islamic economics by emphasizing the importance of integrating Islamic consumer values ​​to encourage ethical economic behavior in the digital era.